Learner Autonomy and Agile Learner on Student Independence and Literacy - Ni Komang Eti Mastini; I Wayan Widiana; I Gusti Ngurah Japa (Journal of Psychology and Instruction, 2022)
There are several problems in the learning process where students are forced to do learning at home. It impacts students' reading and writing literacy which is still low. This study aims to analyze the effect of Learner Autonomy and Agile Learner on the independence and literacy of elementary school students. The type of research used is a quantitative approach with the Ex-Post Facto method. The population was 159 students, using the non-probability sampling technique so that the research sample amounted to 51 students. The data collection method used in this study was a questionnaire. The data collection instrument is in the form of a questionnaire. The data analysis technique used in this research is the quantitative analysis and inferential statistics. The results of data analysis, namely the results of the t-test, are obtained in the coefficients table, which is 3.366, so learner autonomy directly affects student independence. The results of the t-test, obtained in the coefficients table, are 30.446 so that Agile Learner does not directly affect students' metacognition awareness. The coefficients table shows 30.446 showings 0.313, so Learner Autonomy does not directly affect literacy. The coefficients table shows 0.613. So Agile Learner does not directly affect students' literacy. The coefficients table shows 1.68, so independence directly affects students' literacy. It was concluded that students' Learner Autonomy was in a low category, students' Agile Learners were in a low category, students' independence was in the high category, and students' literacy and literacy were in the high category.